Decoding modern consumer societies - Berghoff, Hartmut 1960- HerausgeberIn; Spiekermann, Uwe 1963- HerausgeberIn (Worlds of consumption, 2012)
"The history of consumption has experienced remarkable growth since the 1980s, driven by the interest of scholars in a variety of historical subdisciplines and other social scientific fields. This volume seeks to bring the resultant diversity of specialized approaches into one common discourse. It takes stock of what consumption history has accomplished in recent decades, what current research agendas are, and where research should go from here. Assembled and introduced by Hartmut Berghoff and Uwe Spiekermann of the German Historical Institute in Washington, DC, the volume brings together contributions from scholars in Europe and the United States, who discuss consumption patterns and their implications for the development of modern consumer societies. The geographical scope of these articles encompasses not only both sides of the North Atlantic, but also Argentina, Africa, and Japan. The articles are informed by a variety of approaches, including environmental history, political history, business history, the history of science, cultural history, gender history, intellectual history, and anthropology. The volume is aimed both at specialists in consumption and consumption history as well as at academic readers who wish to familiarize themselves with the field in the first place"--